BIOACCUMULATION OF CADMIUM (CD) BY WHITE SHRIMP PENAEUS MERGUIENSIS AT DIFFERENT SALINITY IN KEDUNGMALANG ESTUARY, JEPARA (CENTRAL JAVA) - Manullang, Corry Yanti; Hutabarat, Johannes; Widowati, Ita (Marine Research in Indonesia, 2014)
Estuarine of Kedungmalang has salinity variability and is assumed to bepolluted by cadmium (Cd) derived from human activities around Kedung region. In this study, bioaccumulation of Cd by white shrimp PenaeusÃÂ merguienis in relation with salinity difference was determined. Sampling was conducted at four stations : estuary (15Ã¢â¬Â° and 25Ã¢â¬Â° of salinity) and husbandry area (15Ã¢â¬Â° and 25Ã¢â¬Â° of salinity). Data on in situ water quality parametersÃÂ was obtained at each station. Absorption Atomic Spectrometer was used to measure Cd concentration. The water quality of parameters and the concentrations of Cd in the shrimp were compared with quality standards and weeklyÃÂ consumption limit of white shrimps is also suggested. The Cd concentrations on the white shrimp was found the highest concentration of 0.669 ÃÂ¼g.g-1 . The limit comsumption of the white shrimp of Estuarine of Kedungmalang,suggested by the resut of this study, is about 523-1537 grams per week.